Using network analysis to map the formal clinical reporting process in pediatric palliative care: a pilot study - Siden, Harold (BioMed Central, 2011)
BACKGROUND: Continuity of care is a key component of care in complex and chronic conditions. Despite its importance, it is often absent in chronic-disease management. One challenge has been identifying tools to measure care continuity. In one context important to families, namely pediatric palliative care, we undertook a project to identify continuity and to pilot the use of network analysis as a tool. METHODS: Network analysis studies patterns of relationships or interactions between members, providing qualitative and quantitative description of network structure. RESULTS: In this report we applied network analysis to paper records of clinical consultations and reports for 6 patients with complex conditions. A high degree of discontinuity was identified, and care was fragmented amongst specialist and generalist providers. Information was shared selectively and often moved in only one direction. CONCLUSIONS: Families have anecdotally reported frustration with poor continuity of care. Network analysis can be a useful tool in describing the discontinuity of care experienced by families dealing with complex and chronic conditions. This tool could be expanded to other systems such as electronic health records and many other health care situations.